Surgical management of advanced oral submucous fibrosis: our experience - Mishra, Girish; Patel, Jaykumar; Sharma, Yojana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Severe oral submucous fibrosis (OSMF) poses problem with maintenance of oral hygiene,detection of malignancies and maintenance of nutrition. Surgical treatment includes release of fibrous bands with or without reconstruction for the raw area and postoperative physiotherapy. Methods: All cases with OSMF who underwent surgical management at our institute were included in our study. The demographic data, preoperative interincisor distance, local examination was recorded. All patients underwent contrast enhanced computed tomography scan of head and neck to rule out hidden malignancy. All cases underwent OSMF band release with or without reconstruction. All patients were instructed for vigorous mouth opening exercise. All patients were followed upto 6 months and further divided into two groups depending upon whether they followed physiotherapy advice or not. Results: 13 patients of age group 18-47 years were included in our study. Male to female ratio was 1.6:1. Pre-operative mean interincisor distance was 7.5 mm whereas post-operative it was 19.5 mm. Patients who had followed mouth opening exercise were having a mean increase of 15 mm more as compared to those who did not. Conclusions: Even after surgical management of severe OSMF, mouth opening exercise remains the key factor for maintenance of mouth opening.